Assessment of Behavioural Markers of Autonoetic Consciousness during Episodic Autobiographical Memory Retrieval: A Preliminary Analysis - M. Irish; B. A. Lawlor; S. M. O'Mara; R. F. Coen (Behavioural Neurology)
There is ongoing theoretical debate regarding episodic memory and how it can be accurately measured, in particular if the focus should be content-based recall of episodic details or something more experiential involving the subjective capacity to mentally travel back in time and “re-live” aspects of the original event. The autonoetic subscale of the Episodic Autobiographical Memory Interview (EAMI) is presented here as a new test instrument that attempts to redress theoretical and methodological shortcomings in autobiographical memory assessment. The EAMI merges a phenomenological detail-based approach with an assessment of autonoetic consciousness, departing considerably from traditional Remember/Know paradigms used within this field. We present findings from an initial pilot study investigating the potential markers of autonoetic consciousness that may accompany episodic retrieval. Key behavioural indices of autonoetic consciousness, notably those of viewer perspective, visual imagery, and emotional re-experiencing, emerged as being inextricably bound with the level of phenomenological detail recalled and the overall re-living judgment. The autonoetic subscale of the EAMI permits conceptually refined assessment of episodic personal memories and the accompanying subjective experience of mental re-living, characteristic of episodic memory.